(untitled) (Current Horticulture, 2024)
Tomato (Lycopersicon esculentum L.) and brinjal (solanum melongena L) is very popular vegetable in India and rich source of antioxidants, minerals and vitamins (Tomar and Saha, 2018). They suffer from several biotic and abiotic stresses. Among these, bacterial wilt caused by Ralstonia solanacearum is most devastating and economically important diseases of both. The several efforts has been taken to overcome these stress. However, grafting was utilized to manage bacterial wilt in tomato crops worldwide (Ganiyu et al., 2018). The use of tolerant rootstocks for grafting brinjalt varieties is most effective approach to control bacterial wilt disease (King et al., 2008). Resistance to R. solanacearum has been identified in various accessions of cultivated brinjal and in distant wild relatives, such as S. capsicoides, S. sisymbriifolium, S. virginianum, S. grandiflorum, S. hispidum, S. sessiliflorum, S. stramonifolium, S. torvum, S. americanum ,S. nigrum, and S. scabrum (Rotino et al., 2014). There are some reports of improving production and productivity in horticultural crops using grafting approach such as guava (Psidium guajava) and pomegranate (Punica granatum) (Nowrozy.,. 2017; Kholia et al., 2022). However, there is no report on in vitro micrografting of tomato, brinjal, chilli, and citrus. Therefore, cost -effective in vitro micrgrafting protocol of tomato, brinjal, chili, and citrus is the need of the day. Micrografted tomato and brinjal against Ralstonia solanacearum using bacterial wilt resistance wild brinjal rootstock, was also evaluated.